Ketamine and olanzapine alter behaviour and prefrontal-cortex BDNF differentially in male and female rats - Kalin Manooki; Mahdieh Gholami; Maryam Eslami; Salar Vaseghi; Batool Ghorbani Yekta (Scientific Reports)
Abstract Schizophrenia is a severe chronic neuropsychiatric disorder with a wide-range of cognitive and mental deficits and different categories of symptoms including positive, negative, and cognitive symptoms. In rodents, sub-chronic ketamine administration is a common method to induce a schizophrenia-like state. Olanzapine, an atypical antipsychotic medication, is used for the treatment and management of schizophrenia symptoms. Here, we aimed to assess the effects of ketamine, olanzapine, and their combination on cognitive and behavioral functions, as well as on brain-derived neurotrophic factor (BDNF) expression in the prefrontal cortex of male and female rats. Ketamine hydrochloride (30 mg/kg, i.p.) was administered for 5 consecutive days to induce schizophrenia-like alterations, and olanzapine (6 mg/kg, i.p.) was administered immediately after the final ketamine dose. Behavioral tests for locomotion, anxiety-like behavior, nociception, compulsive-like behavior, depression-like behavior, and memory were conducted, and BDNF mRNA levels in the prefrontal cortex were measured by quantitative real-time PCR. The results showed that ketamine increased locomotor activity and climbing behavior, decreased rearing (exploration), impaired novel object recognition memory, and lowered BDNF levels in the prefrontal cortex in both sexes. Certain effects of ketamine were sex-specific: ketamine reduced pain threshold (indicating hyperalgesia) and decreased immobility in the forced swim test (suggesting an anti-depressant-like effect) only in females. Olanzapine co-treatment restored locomotor activity and climbing and attenuated memory impairment in both sexes. Olanzapine also increased rearing and normalized pain threshold and immobility in females, indicating a mitigation of ketamine’s female-specific effects. Olanzapine had no significant effect on BDNF levels. In conclusion, ketamine induced a schizophrenia-like phenotype with more pronounced effects in female rats, and olanzapine treatment reversed many of the ketamine-induced behavioral deficits in both sexes. Notably, the therapeutic actions of olanzapine in this model appear to be independent of BDNF upregulation in the prefrontal cortex.